1998
DOI: 10.1162/089892998562834
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of Speech and Auditory Temporal Processing

Abstract: To investigate the role of temporal processing in language lateralization, we monitored asymmetry of cerebral activation in human volunteers using positron emission tomography (PET). Subjects were scanned during passive auditory stimulation with nonverbal sounds containing rapid (40 msec) or extended (200 msec) frequency transitions. Bilateral symmetric activation was observed in the auditory cortex for slow frequency transitions. In contrast, left-biased asymmetry was observed in response to rapid frequency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
185
5
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(217 citation statements)
references
References 20 publications
21
185
5
3
Order By: Relevance
“…Classification times were also significantly faster when the words were presented to the right than to the left auditory channel, t(41) = 2.19, p = .034. The overall pattern was therefore skewed to the right reflecting a general bias due to hemispheric asymmetry with verbal information presented to the right ear being processed more efficiently (e.g., Belin et al, 1998;Kimura, 1961).…”
Section: Resultsmentioning
confidence: 99%
“…Classification times were also significantly faster when the words were presented to the right than to the left auditory channel, t(41) = 2.19, p = .034. The overall pattern was therefore skewed to the right reflecting a general bias due to hemispheric asymmetry with verbal information presented to the right ear being processed more efficiently (e.g., Belin et al, 1998;Kimura, 1961).…”
Section: Resultsmentioning
confidence: 99%
“…One such study was carried out by Belin et al (1998) who used positron emission tomography (PET) to examine processing of formant transitions of different durations in pseudospeech syllables. The principal finding was that whereas left auditory cortical response was similar to both slower and faster transitions, the right auditory cortex responded best to the slower transitions, indicating a differential sensitivity to speed of spectral change.…”
Section: Evidence That Simple Acoustic Features Of Sounds Can Explainmentioning
confidence: 99%
“…Functional imaging studies using PET or fMRI in healthy adults have demonstrated that the response to rapid auditory stimuli, in the form of rapid frequency transitions, is greater over the left hemisphere than the right, highlighting the importance of the left hemisphere for the processing of auditory information containing rapid transitions (Belin et al, 1998;Zaehle et al, 2004). Zaehle and colleagues reported exclusively left-sided activations in Heschl's gyrus and the planum temporale associated with the perception of both short gaps and stop consonant-vowel syllables.…”
Section: Functional Neuroimaging Studiesmentioning
confidence: 99%